P1746EFFICACY OF EXTRACORPOREAL PHOTOPHERESIS FOR THE TREATMENT OF RENAL CHRONIC ANTIBODY MEDIATED REJECTION: A PILOT STUDY. (6th June 2020) - Pattonieri, Eleonora Francesca; Gregorini, Marilena; Viarengo, Gianlcuca; Del Fante, Claudia; Perotti, Cesare; Grignano, Maria Antonietta; Sepe, Vincenzo; Libetta, Carmelo; Abelli, Massimo; Ticozzelli, Elena; RAmpino, Teresa
Abstract: Background and Aims: Chronic antibody-mediated rejection (cABMR) is the main cause of kidney allograft failure. Currently there is no effective treatment. Extracorporeal photopheresis (ECP) is an immunomodulating therapy that acts increasing regulatory T cells and reducing effector T cells. ECP has been used with success to treat heart and lung rejection, acute and chronic Graft versus Host Disease and few cases of acute antibody mediated kidney rejection. The aim of this study was to describe the preliminary experience of ECP use to treat kidney cABMR. Method: This is an ongoing prospective observational study approved by the ethical committee of our institution. The study started in 2017 on kidney transplant recipients (KTR) with cABMR diagnosis bioptically proved. All patients received ECP in addition to the standard treatment. ECP schedule is reported in Figure 1. Serum and urine samples were collected at the beginning of the study and every 6 months during the follow up period. Analyzed variables were: glomerular filtration rate (GFR), urine albumin-creatinine ratio (UACR), Donor Specific Antibodies (DSA) measeured as Mean Intensity Fluorescence (MIF) by Luminex. Collected clinical data included: death, hospital admission number, cancer diagnosis, infections. Quality of life (QoL) scale was also recorded. Results: We enrolled 6 KTR equally distributed in gender (3 M, 3 F) and aged 49.16 ± 7.15 years (mean±ds) . Median follow up time was 12 months (min 12 – max 36). All KTR had both class I and class II DSA with MFI > 5000 (min 5000 – max 36780). In all patients no GFR deterioration was observed during follow up. UACR improved in 3 KTR while remained stable in the other 3 patients. No deaths or infections or cancer diagnosis or hospital admissions occurred. QoL ameliorated in all KTR. DSA MIF decreased in all KTR and in 3 of them became even negative after 12 months of treatment. Conclusion: ECP is a safe and effective treatment to slow down the deterioration of kidney function in cABMR patients. Further studies are necessary to identify the responder patients and to better tailor the treatment schedule.